Morphological characterization and genetic diversity of a new microsporidium, Neoflabelliforma dubium n. sp. from the adipose tissue of Diaphanosoma dubium (Crustacea: Sididae) - Weng, Meiqi; Zhang, Xintong; Xin, Zhaozhe; Xue, Sijia; Zhang, Qianqian; Li, Aihua; Zhang, Jinyong (Frontiers in Cellular and Infection Microbiology, 2023)
We reported a new microsporidium Neoflabelliforma dubium n. sp. from the adipose tissue of Diaphanosoma dubium in China. The infected daphnids generally appeared opaque due to the presence of numerous spore aggregates located in the adipose tissue. All developmental stages were in direct contact with the host cell cytoplasm. Multinucleate sporogonial plasmodia developed into uninucleate sporoblasts by rosette-like fashion. Mature spores were pyriform and monokaryotic, measuring 4.02 ± 0.24 (3.63-4.53) µm long and 2.27 ± 0.15 (2.12-2.57) µm wide (N = 40). The polaroplast was bipartite with a tightly packed anterior lamellae and a loosely aligned posterior lamellae. Isofilar polar filament was coiled 9-11 turns and arranged in 2-3 rows. The phylogenetic analysis based on the obtained SSU rDNA sequence indicated that the N. dubium n. sp. clustered with the freshwater oligochaete-infecting N. aurantiae to form an independent monophyletic group, positioned at the base of Clade 4. In addition, we analyzed the genetic diversity in three N. dubium n. sp. isolates based on the rDNA (SSU rDNA, ITS and LSU rDNA) and Rpb1 gene. The genetic variation among the rDNA sequences was not distinct, however, high nucleotide diversity could be observed in Rpb1 gene, and a wide variety of Rpb1 haplotypes were identified within each isolate. Genetic recombination detected in the Rpb1 sequences presumes cryptic sexual process occurring in N. dubium n. sp. Statistical evolutionary analyses further indicated that the purifying selection eliminated mutations in the Rpb1 gene.